"Colloid‐Rich" follicular neoplasm/suspicious for follicular neoplasm thyroid fine‐needle aspiration specimens: Cytologic, histologic, and molecular basis for considering an alternate view. Issue 12 (23rd July 2013) - Ohori, N. Paul; Wolfe, Jenna; Hodak, Steven P.; LeBeau, Shane O.; Yip, Linwah; Carty, Sally E.; Duvvuri, Umamaheswar; Schoedel, Karen E.; Nikiforova, Marina N.; Nikiforov, Yuri E.
Abstract : BACKGROUND: Typically, thyroid follicular neoplasm/suspicious for follicular neoplasm (FN/SFN) cases show moderate to marked cellularity and scant or absent colloid. Recently, cases have been noted with microfollicular cellularity in the background of moderate to abundant amount of colloid. The purpose of this study was to compare these "colloid‐rich" FN/SFN cases to the typical FN/SFN cases. METHODS: Thyroid cytology specimens with the features of FN/SFN were searched in cytopathology files from September 2008 to June 2012. Cases with absent or minimal colloid were designated "typical colloid‐poor" FN/SFN and cases with moderate to abundant colloid were designated "colloid‐rich" FN/SFN. From these cases, those with surgical pathology resection follow‐up were identified. Cytologic, surgical pathology resection, and molecular features ( BRAF, RAS, RET/PTC, and PAX8‐PPARγ ) were investigated for the typical colloid‐poor FN/SFN cases and were compared with those of the colloid‐rich FN/SFN cases. RESULTS: Of 431 FN/SFN cases with surgical pathology resection follow‐up, 360 (83.5%) cases showed features of typical colloid‐poor FN/SFN and 71 (16.5%) cases showed features of colloid‐rich FN/SFN. Papillary carcinoma was the most common malignant outcome for the 2 groups. Although the proportion of malignant outcome was similar for the 2 groups, the "colloid‐rich" FN/SFN cases showed a greater proportion of nodular hyperplasia among the cases with benign outcome. In addition, the "colloid‐rich" FN/SFN cases demonstrated a greater proportion of cases with a mutation. CONCLUSIONS: Approximately one‐sixth of cases of FN/SFN show "colloid‐rich" features. Comparison to the typical colloid‐poor FN/SFN demonstrated similar risk for malignancy but contrasting resection outcome and molecular characteristics. Cancer (Cancer Cytopathol) 2013;121:718–728 . © 2013 American Cancer Society . Abstract : Approximately one‐sixth of follicular neoplasm/suspicious for follicular neoplasm (FN/SFN) cases show "colloid‐rich" features. "Colloid‐rich" FN/SFN cases demonstrate similar risk of malignancy to that of the typical FN/SFN cases but differences in resection outcome and molecular characteristics.